Development of a biotic integrity index based on long-term fish assemblage changes after dam construction in China - Zhu, Di; Yang, Zhi; Chen, Xiaojuan; Jin, Yao; Li, Dewang (Frontiers in Environmental Science, 2023)
Multi-metric indicators based on fish assemblages have been widely applied to assess aquatic ecosystem biotic integrity. However, many of these were not detailed or standardized in metrics selection and reference status for a reservoir ecosystem under the long-term effects of hydro-electrical dam development. This makes it very difficult to determine the reference status and metrics because fish assemblages have been affected by human activities such as large reservoir operations. Based on long-term fish assemblage data, there were significant differences in fish composition between backwater and reservoir areas ten years after the Three Gorges Reservoir (TGR) formation in China. We conducted this study to develop a new fish IBI to evaluate a large river reservoir ecosystem based on long-term monitoring data by establishing subregional habitat reference and selecting sensitive and concise metrics. In the TGR, we found that: (1) dynamic change is an important feature of fish assemblages in a relatively dynamic state after a decade of intensive disturbance caused by reservoir operations; (2) reference conditions for the reservoir evaluation should be selected in different stages for two different ecological habitats (lotic backwater and lentic reservoir reaches); (3) two core metrics and five sensitive metrics were selected to reflect fish assemblage degradation based on long term observations; and (4) overall fish biological integrity is generally "fair-poor", in the reservoir area it is "fair" and "poor", and in the reservoir lotic backwater it is "fair". The long-term effects of large canyon reservoirs on biological integrity require long-term observation, and reasonable recovery targets should be set at different stages in reservoir management. In this study, a new biological integrity index was developed to screen and evaluate the ecological status of a semi-artificial reservoir ecosystem. Our results support reservoir biologically integrated management and green sustainable development goals.